Antibacterial Effects of Tobacco Leaf Extract (Nicotiana tabacum) on Fusobacterium nucleatum (in vitro Study) - Michelle Wilsan; Wiena Widyastuti; Dewa Made Wedagama (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Deep caries can involve the pulp tissue, necessitating pulp capping treatment. Fusobacterium nucleatum is frequently found in deep caries. One of the essential requirements for pulp capping materials is antibacterial properties. Mineral Trioxide Aggregate (MTA) is a commonly used pulp capping material due to its favorable characteristics, such as antibacterial properties, biocompatibility, and more. However, MTA has several drawbacks, including a long setting time, difficult manipulation, risk of staining and discoloration, and high cost. Nicotiana tabacum leaf extract has the potential to serve as an herbal alternative for pulp capping materials, as it is known to possess antibacterial properties derived from its secondary metabolites. This study aimed to determine the antibacterial effects of Nicotiana tabacum leaf extract on Fusobacterium nucleatum. Materials and Methods: An in vitro experimental laboratory study with a post-test only control group design was conducted. The antibacterial test used the 96-well microdilution and plate count methods to determine Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). There were nine test groups, consisting of Nicotiana tabacum leaf extract at 3.125%, 6.25%, 12.5%, 25%, and 50% of 1000 µg/µL (31.25 µg/µL, 62.5 µg/µL, 125 µg/µL, 250 µg/µL, and 500 µg/µL), sterile aquadest (negative control), MTA (positive control), and internal controls (Nicotiana tabacum leaf extract and sterile aquadest). Results: The number of bacterial colonies significantly decreased as the extract concentration increased. Nicotiana tabacum leaf extract showed MIC values at 12.5% (125 µg/µL) and MBC values at 25% (250 µg/µL). The antibacterial activity of Nicotiana tabacum leaf extract is attributed to its secondary metabolites, including flavonoids, saponins, steroids, and triterpenoids, which disrupt bacterial structures and functions. Conclusion: Nicotiana tabacum leaf extract has antibacterial effects (bacteriostatic and bactericidal) on Fusobacterium nucleatum.